2022
DOI: 10.24275/rmiq/ia2680
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of agro-industrial waste: Anaerobic lagoons in Latin America

Abstract: totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Anaerobic digestion (AD) has had an increasing relevance in recent years as a renewable energy source utilizing organic residues (e.g., manure, food waste, and crop residues) (Scarlat et al, 2018). Galvan-Arzola et al (2022) reported that nitrogen inhibition of AD plays an important role in Latin America. AD is a complex multistage process performed by different groups of microorganisms in oxygen absence.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion (AD) has had an increasing relevance in recent years as a renewable energy source utilizing organic residues (e.g., manure, food waste, and crop residues) (Scarlat et al, 2018). Galvan-Arzola et al (2022) reported that nitrogen inhibition of AD plays an important role in Latin America. AD is a complex multistage process performed by different groups of microorganisms in oxygen absence.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, treatment systems for these smallholder facilities must be inexpensive, easy to operate and maintain. Some systems evaluated and in use to treat this type or similar agro-industrial effluents that have high pollutant loads include aerobic and anaerobic systems with different configurations (Hernandez-Fydrych et al, 2021;Galván-Arzola et al, 2022) and some ecological systems such as constructed wetlands (CWs) (Hu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%